2009
DOI: 10.2174/187152009787047743
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolo[2,1-c][1,4]benzodiazepine as a Scaffold for the Design and Synthesis of Anti- Tumour Drugs

Abstract: Compounds that bind in the minor groove of DNA have found use in the experimental treatment of cancer and certain infectious diseases. Furthermore, agents which target and can recognize discrete sequences of DNA have the potential to offer selective therapies by modulating the activity of specific transcription factors or genes. For this reason, a number of sequence-selective DNA binding agents have been evaluated with a range of affinities and recognition fidelities. In this respect, the pyrrolo[2,1-c][1,4]be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
54
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 107 publications
0
54
0
Order By: Relevance
“…KEYWORDS Pyrrolo[2,1-c] [1,4]benzodiazepine (PBD), antitumor agents, GWL-78, DNA, minor-groove binder T he pyrrolo [2,1-c] [1,4]benzodiazepines (PBDs) are a well-known class of sequence-selective covalent-binding DNA-interactive agents [1][2][3][4] that fit perfectly in the minor groove of DNA due to their chiral C11a(S)-position, which provides a right-handed longitudinal twist isohelical with double-stranded DNA. 3 They also possess an electrophilic N10-C11 imine moiety (or the carbinolamine or carbinolamine methyl ether equivalent) that can form a covalent aminal linkage between their C11-position and the nucleophilic C2-NH 2 group of a guanine base.…”
mentioning
confidence: 99%
“…KEYWORDS Pyrrolo[2,1-c] [1,4]benzodiazepine (PBD), antitumor agents, GWL-78, DNA, minor-groove binder T he pyrrolo [2,1-c] [1,4]benzodiazepines (PBDs) are a well-known class of sequence-selective covalent-binding DNA-interactive agents [1][2][3][4] that fit perfectly in the minor groove of DNA due to their chiral C11a(S)-position, which provides a right-handed longitudinal twist isohelical with double-stranded DNA. 3 They also possess an electrophilic N10-C11 imine moiety (or the carbinolamine or carbinolamine methyl ether equivalent) that can form a covalent aminal linkage between their C11-position and the nucleophilic C2-NH 2 group of a guanine base.…”
mentioning
confidence: 99%
“…397 We also performed clonogenic cell survival assays to confirm 398 the cytotoxicity of compounds in DLD-1 and HepG2 cancer cells 399 and found that both compounds caused cytotoxicity at P10 lM 400 concentration as shown in Fig. 4C and D. It is also interesting to note that the earlier known PBD molecules 456 exerted their anticancer effect by binding with DNA and hence were 457 non-specific in nature [15,32,33]. The C-11 position of the 458 7-membered ring was responsible for DNA binding [34][35][36].…”
mentioning
confidence: 92%
“…66 Defects in DNA ligation can cause increased genomic instability and 67 hypersensitivity to DNA damaging agents leading to cellular lethal-68 ity [9][10][11]. However, genomic instability can also give rise to uncon- broad spectrum biological activities such as antibacterial, antileish-80 manial, herbicidal and anticancer agents [13][14][15] The PBD derivatives described [17] were drawn using Sketch 117 module of Sybyl7.1. The compound structures for docking were 118 prepared by geometry optimization using a combination of the 119 MMFF94 force field of the SYBYL molecular modeling package with 120 Powell energy minimization algorithm, Gasteiger-Huckel charges, 121 and 0.001 kcal/(mol Å) energy gradient convergence criterion.…”
mentioning
confidence: 99%
“…Anthramycin 3 and its analogues, on the other hand, are isolated from Streptomyces strains, possess the tricyclic pyrrole [2,1-c] [1,4]benzodiazepine scaffold and exhibit a unique feature-alkylation of the minor groove of DNA. This feature is caused by appropriate geometry and the presence of binding groups such as an imine, a carbinolamine, or a carbinolamine ether group [3].…”
Section: Introductionmentioning
confidence: 99%